Utilization of Solid Residue Melaleuca cajuputi Powell Leaves as Cattle Feed - Widiana, Ana; Taufikurahman; Limin, S.H.; Hernaman, I.; Hernaman, I.; Manurung, R. (Pakistan Journal of Nutrition, 2014)
Distillation process of M. cajuputi Powell leaves to produce cajuput oil, yields a large amount of solid residue as waste materials. In vitro testing was conducted to evaluate the potential of solid residue of M. cajuputi Powell leaves as cattle feed. The measured variables were NH3, volatile fatty acids (VFA), Dry Matter Digestibility (DMD), and Organic Matter Digestibility (DMO). Completely randomized design was made with 5 different treatments and 4 replications, in order to get 20 experimental units. Data was analyzed by analysis of variance (ANOVA), followed by Duncan's multiple range test with a significance level of 5%. The results showed that giving 100% of the solid residue of M. cajuputi Powell leaves produced VFA, DMD and DMO for about 102.25 mM, 59.75% and 42.28% respectively, but with lesser amount of NH3 (2.54mM). These results were significant (P < 0.05) and are higher than the results by using field grass. It can be concluded that the solid residue of M. cajuputi Powell leaves has the potential to be used as cattle feed.